Development of Discovery Learning-Based History E-Modules in Class XI History Learning at the Senior High School Level - Santia, Meli; Meldawati, Meldawati; Junaidi, Juliandry Kurniawan (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
This research aims to develop a learning media in the form of a discovery learning-based history e- module in grade XI history learning at the high school level. This type of research is Research and Development (research and development). The development model used is the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The results of this study indicate that the e-modules developed are valid and practical with details: First, the material in the e-module developed is categorized as very valid with a percentage of 95.2%. In the media aspect, it got a very valid category with a percentage of validity reaching 93.6% and the validity of the language aspect also got a very valid category with a percentage of validity of 94.6%. Second, the developed history e-module is in the very practical category with a final score percentage of 85.33% and 89.80%, respectively obtained from the analysis of teacher and learner practicality questionnaire data. Based on the explanation above, it can be concluded that the discovery learning-based history e-module in class XI history learning at the high school level developed is feasible to use in the learning process.